Error Model and Accuracy Calibration of 5-Axis Machine Tool - Fangyu Pan; Ming Li; Jian Yin (Institute of Advanced Engineering and Science, 2013)
To improve the machining precision and reduce the geometric errors for 5-axis machinetool, error model and calibration are presented in this paper. Error model is realized by the theory of multi-body system and characteristic matrixes, which can establish the relationship between the cutting tool and the workpiece in theory. The accuracy calibration was difficult to achieve, but by a laser approach-laser interferometer and laser tracker, the errors can be displayed accurately which is benefit for later compensation. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3022